A parametrically excited vibration energy harvester. (February 2014) - Jia, Yu; Yan, Jize; Soga, Kenichi; Seshia, Ashwin A
In the arena of vibration energy harvesting, the key technical challenges continue to be low power density and narrow operational frequency bandwidth. While the convention has relied upon the activation of the fundamental mode of resonance through direct excitation, this article explores a new paradigm through the employment of parametric resonance. Unlike the former, oscillatory amplitude growth is not limited due to linear damping. Therefore, the power output can potentially build up to higher levels. Additionally, it is the onset of non-linearity that eventually limits parametric resonance; hence, this approach can also potentially broaden the operating frequency range. Theoretical prediction and numerical modelling have suggested an order higher in oscillatory amplitude growth. An experimental macro-sized electromagnetic prototype (practical volume of ~1800 cm3) when driven into parametric resonance, has demonstrated around 50% increase in half power band and an order of magnitude higher peak power density normalised against input acceleration squared (293 µW cm −3 m −2 s 4 with 171.5 mW at 0.57 m s −2 ) in contrast to the same prototype directly driven at fundamental resonance (36.5 µW cm −3 m −2 s 4 with 27.75 mW at 0.65 m s −2 ). This figure suggests promising potentials while comparing with current state-of-the-art macro-sized counterparts, such as Perpetuum's PMG-17 (119 µW cm −3 m −2 s 4 ).